2000
DOI: 10.1096/fasebj.14.9.1233
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and globular amyloid β protein (1–42) induces rapid cellular degeneration: evidence for AβP channel‐mediated cellular toxicity

Abstract: Amyloid beta peptides (AbetaP) deposit as plaques in vascular and parenchymal areas of Alzheimer's disease (AD) tissues and Down's syndrome patients. Although neuronal toxicity is a feature of late stages of AD, vascular pathology appears to be a feature of all stages of AD. Globular and nonfibrillar AbetaPs are continuously released during normal cellular metabolism, form calcium-permeable channels, and alter cellular calcium level. We used atomic force microscopy, laser confocal microscopy, and calcium imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
178
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(201 citation statements)
references
References 57 publications
21
178
2
Order By: Relevance
“…The second type includes oligomers of 25-40-mers size; their binding to amyloid specific dyes thioflavine T and Congo red and the development of far UV CD spectrum similar to the fibrillar CD signal indicate the formation of cross-b-sheet structure. Both types of oligomers exhibit similar roundshaped morphology in AFM images which is commonly associated with prefibrillar amyloid [1][2][3][4][5]. Here we have demonstrated that only the second enlarged type of oligomers produce cytotoxic effect on two kinds of neuronal cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The second type includes oligomers of 25-40-mers size; their binding to amyloid specific dyes thioflavine T and Congo red and the development of far UV CD spectrum similar to the fibrillar CD signal indicate the formation of cross-b-sheet structure. Both types of oligomers exhibit similar roundshaped morphology in AFM images which is commonly associated with prefibrillar amyloid [1][2][3][4][5]. Here we have demonstrated that only the second enlarged type of oligomers produce cytotoxic effect on two kinds of neuronal cells.…”
Section: Discussionsupporting
confidence: 60%
“…However the definition of the toxic amyloid species and their particular structural properties exerting the specific cytotoxic effect remain controversial. In the last years a number of studies have supported the hypothesis that early aggregates or prefibrillar species are implicated in cytotoxicity while fibrillar amyloid deposits serve as an escape route for smaller aggregates [1][2][3][4][5]. Among them Kayed et al observed that intermediate-size water soluble oligomers of Ab and other five proteins form sheared structures characterized by similar conformational epitope, suggesting that they exert cytotoxicity via similar mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus of great interest to elucidate the physiological role of Ah under normal conditions. At present, the physiological role of Ah is not clear, but suggestions include a neurotrophic action at a low concentration (Chauhan et al, 1991), enhancement of N-methyl-D-aspartate (NMDA) receptormediated current (Furukawa and Mattson, 1998;Harkany et al, 2000) and long-term potentiation (Ishida et al, 1997), enhancement of AMPA receptor-mediated current (Blanchard et al, 1997), formation of calcium channels (Bhatia et al, 2000), and effects on intracellular calcium homeostasis (Bhatia et al, 2000;Mattson et al, 1993). Most of these suggestions need to be confirmed, and it is not clear whether the suggested actions of Ah can be mediated by physiological concentrations of Ah.…”
Section: Discussionmentioning
confidence: 99%
“…The target of the A␤ peptide in biological and model membranes is phosphatidylserine (PS), the proapoptic signaling phospholipid (37). Subsequently the calcium channel properties of A␤ have been verified in many other laboratories (38)(39)(40)(41)(42). We and others have therefore hypothesized that calcium conducted into the target neurons by the A␤ channel might be responsible for A␤ neurotoxicity.…”
mentioning
confidence: 82%